2021
DOI: 10.3390/biom11030376
|View full text |Cite
|
Sign up to set email alerts
|

Insights from Cardiopulmonary Exercise Testing in Pediatric Patients with Hypertrophic Cardiomyopathy

Abstract: The usefulness of cardiopulmonary exercise test (CPET) in adult hypertrophic cardiomyopathy (HCM) patients is well-known, whereas its role in pediatric HCM patients has not yet been explored. The present study investigates possible insights from a CPET assessment in a cohort of pediatric HCM outpatients in terms of functional and prognostic assessment. Sixty consecutive pediatric HCM outpatients aged <18 years old were enrolled, each of them undergoing a full clinical assessment including a CPET; a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Nevertheless, before attributing low values of VO 2 p and oxygen pulse to sedentary lifestyle or muscle deconditioning alone, caution is necessary. Frankly, low values of VO 2 p could hide residual cardiovascular and respiratory distress, and it is known that VO 2 p is an independent risk factor associated with poor prognosis in several diseases [ 10 , 26 , 27 ] and all-cause mortality in the general population [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, before attributing low values of VO 2 p and oxygen pulse to sedentary lifestyle or muscle deconditioning alone, caution is necessary. Frankly, low values of VO 2 p could hide residual cardiovascular and respiratory distress, and it is known that VO 2 p is an independent risk factor associated with poor prognosis in several diseases [ 10 , 26 , 27 ] and all-cause mortality in the general population [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small, single-center studies that focused on cardiopulmonary exercise testing (CPET) have shown, in univariable analyses, that the percentage of predicted peak oxygen consumption (V o 2 ) has a strong association with heart failure mortality and SCD in pediatric HCM. 3 In adults, the role of exercise stress testing has been further delineated. CPET measures, incorporated into prediction models, have been useful in determining risk of heart failure, SCD, and stroke-related events.…”
mentioning
confidence: 99%